PENGARUH FAMILY WORK CONFLICT DAN KOMPENSASI FINASIAL PADA KEPUASAN KERJA SERTA PENGARUH KEPUASAN KERJA PADA KINERJA KARYAWAN WANITA BAGIAN FRONTLINER BANK DI JABODETABEK - Fellia Elsa Garini; Ossi Ferli (Ibs Press, 2024)
This study aims to test and determine the effect of family work conflict and financial compensation on job satisfaction and determine the effect of job satisfaction on performance. The independent variables in this study are employee performance and job satisfaction. The data collection technique used in this study was a questionnaire distributed online using a googleform link which then the researcher managed to get a sample of 95 respondents who were employees who were either married or not who worked at the Frontliner Bank as CS or Teller. The results in this study show that family work conflict has no negative effect on job satisfaction, and financial compensation has a positive and significant effect on job satisfaction and job satisfaction has a positive and significant effect on performance.